2008
DOI: 10.1007/s00296-008-0614-8
|View full text |Cite
|
Sign up to set email alerts
|

Value of anti-mutated citrullinated vimentin antibodies in diagnosing rheumatoid arthritis

Abstract: We assessed the diagnostic value of anti-mutated citrullinated vimentin antibodies (anti-MCV) and compared it with those of anti-cyclic citrullinated peptide antibodies (anti-CCP), IgA (ARF), IgM (MRF) and IgG (GRF) rheumatoid factors for rheumatoid arthritis (RA). Serum samples of 170 RA patients, with early and established RA, and 309 controls were tested for anti-MCV, anti-CCP, ARF, MRF and GRF using commercially available ELISA kits. Cut off of different tests was determined with ROC curves. The sensitivit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
47
0
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 50 publications
(56 citation statements)
references
References 13 publications
6
47
0
1
Order By: Relevance
“…[14] Studies have shown that anti-CCP assay appears to be superior to the anti-MCv test in the diagnostic performance of RA. [2,3] ın their study which followed patients with early RA, Mathsson et al [4] reported that changes in the anti-MCv level showed a stronger correlation with changes in clinical parameters than it did with changes in the anti-CCP level. The presence of anti-MCv was predictive of subsequent high disease activity and continued radiographic progression in early RA.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[14] Studies have shown that anti-CCP assay appears to be superior to the anti-MCv test in the diagnostic performance of RA. [2,3] ın their study which followed patients with early RA, Mathsson et al [4] reported that changes in the anti-MCv level showed a stronger correlation with changes in clinical parameters than it did with changes in the anti-CCP level. The presence of anti-MCv was predictive of subsequent high disease activity and continued radiographic progression in early RA.…”
Section: Discussionmentioning
confidence: 99%
“…[1] These antibodies may serve as a powerful serologic marker for early diagnosis and prognostic prediction of RA. [2,3] While the specificity of these tests is above 90%, sensitivity varies between 33% and 87.2%. [1] Recently, studies have been reported that are associated with the poor radiographic prognosis of anti-mutated citrullinated vimentin (anti-MCv).…”
mentioning
confidence: 99%
“…Subsequently, a human recombinant mutated isoform of vimentin, citrullinated in vitro, was used in a new commercial enzyme-linked immunosorbent assay (ELISA) for detection of the respective antibodies against mutated citrullinated vimentin (anti-MCV) (12). Studies that compared the diagnostic accuracy of anti-MCV and anti-CCP antibodies in RA found comparable sensitivities, while the specificities were higher for anti-CCP in most cases (13)(14)(15)(16)(17)(18)(19). In contrast to RA, the occurrence of antibodies targeting citrullinated proteins, especially anti-MCV antibodies in rheumatic diseases of childhood, has remained largely unknown (20)(21)(22).…”
Section: Introductionmentioning
confidence: 99%
“…The other novel autoantibody test, anti-MCV, targets modified citrullinated vimentin and has its origin in the older anti-Sa autoantibody test that has been shown to target citrullinated vimentin (13). Compared with anti-CCP-2, studies have demonstrated somewhat lower specificities and higher sensitivities for RA when anti-MCV is used (79-92% and 70-84%, respectively) (4)(5)(6)14).…”
mentioning
confidence: 99%
“…The anti-cyclic citrullinated peptide (anti-CCP) test, which is directed against a synthetic citrullinated peptide, revealed a higher specificity for RA when the first-generation anti-CCP (anti-CCP-1) test was used in comparison with the RF test (91-96% versus 74-91%) (3)(4)(5)(6)(7). Subsequently, a commercially available second-generation anti-CCP test (anti-CCP-2) was developed, showing an even better specificity for RA (90-97%) (4)(5)(6)(7)(8)(9). RF and anti-CCP-2 autoantibodies can also be present in the preclinical phase and are associated with future RA development (10,11).…”
mentioning
confidence: 99%